2008
DOI: 10.1158/0008-5472.can-07-2946
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, Insulin-like Growth Factor-I, Endogenous Estradiol, and Risk of Colorectal Cancer in Postmenopausal Women

Abstract: Obesity is a risk factor for colorectal cancer, and hyperinsulinemia, a common condition in obese patients, may underlie this relationship. Insulin, in addition to its metabolic effects, has promitotic and antiapoptotic activity that may be tumorigenic. Insulin-like growth factor (IGF)-I, a related hormone, shares sequence homology with insulin, and has even stronger mitogenic effects. However, few prospective colorectal cancer studies directly measured fasting insulin, and none evaluated free IGF-I, or endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
181
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(199 citation statements)
references
References 44 publications
12
181
5
1
Order By: Relevance
“…OCC hormones may also suppress of insulin like growth factor I and synthesis or secretion of bile acids, which are inversely associated with the risk of CRC [28].…”
Section: Discussionmentioning
confidence: 99%
“…OCC hormones may also suppress of insulin like growth factor I and synthesis or secretion of bile acids, which are inversely associated with the risk of CRC [28].…”
Section: Discussionmentioning
confidence: 99%
“…IR is a condition in which the body produces sufficient insulin to take up and use glucose, but the sensitivity to this insulin is impaired or selective, thus causing pancreatic b-cells to upregulate insulin production as a compensatory mechanism, which results in hyperinsulinemia. There are several studies linking hyperinsulinemia and the risk and/or aggressiveness of colorectal, pancreatic, liver, esophageal, breast, and endometrial cancers (Gunter et al 2008, Arcidiacono et al 2012, Inoue & Tsugane 2012, Qiu et al 2012, Zhan et al 2013. Thyroid nodules follow the same trend (Rezzonico et al 2008).…”
Section: Ir and The Role Of Igf1mentioning
confidence: 99%
“…A small number of prospective epidemiologic studies have looked at IGF-I and IGFBP-3 as risk factors for of colorectal cancer (7)(8)(9)(10)(11)(12)(13)(14). These studies have generally indicated an increased risk of disease with higher concentrations of IGF-I, although only two of these results (7,9) were statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have generally indicated an increased risk of disease with higher concentrations of IGF-I, although only two of these results (7,9) were statistically significant. For IGFBP-3, the picture is considerably less clear with two studies showing strong inverse associations (7,9), whereas most others produced results suggestive of positive associations between IGFBP-3 concentration and incident colorectal cancer (7)(8)(9)(10)(11)(12)(13)(14). Only one study has looked prospectively at colorectal adenomas, and although Giovannucci and colleagues (7) found no evidence that elevated IGF-I or IGFBP-3 were associated with nonadvanced adenomas, they did observe strong associations between each of these serum measures and advanced adenoma.…”
Section: Introductionmentioning
confidence: 99%